Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Is my approach to evaluating this series correct?

$$\sum_{n=1}^\infty \frac{n}{(n+1)!}$$

Has partial sum equivalent to:

$$S_m = \sum_{n=1}^m \frac{n}{(n+1)!} = \sum_{j=2}^{m+1} \frac{j-1}{j!} = \sum_{j=2}^{m+1} \frac{1}{(j-1)!} - \sum_{j=2}^{m+1} \frac{1}{j!} $$

For $j$ such that $m+1>j>2$ the terms of the left sum are cancelled by the terms of the right, leaving

$$ S_m =1-\frac{1}{(m+1)!}$$

Hence $ \lim_{m\rightarrow\infty} S_m = 1$

Apologies for this one. The book I am using hasn't really offered anything on series with factorial denominators (yet). Thanks!

share|cite|improve this question
Looks fine to me. – Brian M. Scott Jan 5 '13 at 23:59
I see nothing wrong. I'm editing to improve formatting, however. – Alex Becker Jan 6 '13 at 0:03
It should be $S_m$ everywhere – leo Jan 6 '13 at 0:04
+1 Nice......... – DonAntonio Jan 6 '13 at 3:55
up vote 4 down vote accepted

Your solution is not only correct but also a very nice one.

Once you know the closed form for the partial sum, you can also prove it by induction, starting with $S_1=1-1/2=1/2$ and taking the induction step

$$ \begin{align} S_{m+1}&=S_m+\frac{m+1}{(m+2)!} \\ &=1-\frac1{(m+1)!}+\frac{m+1}{(m+2)!} \\ &=1+\frac{m+1-(m+2)}{(m+2)!} \\ &=1-\frac1{(m+2)!}\;. \end{align} $$

share|cite|improve this answer
Cheers Joriki - hadn't actually thought of trying it by induction. – conjectures Jan 6 '13 at 10:14

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.